2012
DOI: 10.1634/theoncologist.2011-0216
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Oral Cavity in Nonsmoking Women: A New and Unusual Complication of Chemotherapy for Recurrent Ovarian Cancer?

Abstract: After completing this course, the reader will be able to:1. Compare the risk of secondary cancer versus benefits of maintenance therapy for women with ovarian cancer who have a complete response to pegylated liposomal doxorubicin.2. Explain the need to perform regular and frequent oral examinations in women with ovarian cancer who received treatment with pegylated liposomal doxorubicin.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTPurpose. To descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Despite the great advances achieved in surgery and in chemoradiotherapy technology recently, patients who have had TSCC have a high risk of developing secondary or recurrent tumors in the surrounding area. Moreover, in patients with lymph nodes spread, the 5-year overall survival rate does not exceed 50 % [2,3]. Therefore, cancer screening and early detection have major importance in the survival of TSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great advances achieved in surgery and in chemoradiotherapy technology recently, patients who have had TSCC have a high risk of developing secondary or recurrent tumors in the surrounding area. Moreover, in patients with lymph nodes spread, the 5-year overall survival rate does not exceed 50 % [2,3]. Therefore, cancer screening and early detection have major importance in the survival of TSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a literature review, with the exception of HIV-related Kaposi sarcoma, all patients who developed oromaxillary SCC after long-term use of PLD had mullerian cancer, suggesting a cancer-specific linkage [1,2]. However our case was endometrial cancer, thus implying that this complication is also relevant to malignancies other than mullerian cancer.…”
mentioning
confidence: 72%
“…We read the article by Cannon et al [1] with great interest. The authors reported five ovarian and fallopian tubal cancer patients who developed oromaxillary squamous cell carcinoma (SCC) during long-term maintenance therapy with pegylated liposomal doxorubicin (PLD) (range, 30 -132 months; cumulative dose, 1,696 -3,000 mg/m 2 ).…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The development of secondary malignancies, predominantly lymphomas, has also been reported in HIV-positive patients treated for Kaposi sarcoma 5. Recently, five cases of squamous cell carcinoma (SCC) of the oral cavity have been described in a case series of patients treated with long-term PLD who were non-smokers and with no known risk factors for human papillomavirus (HPV) 6. In this report we describe a further case of SCC in a woman with no other risk factors who was treated for more than 6 years with PLD for a recurrent ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%